A prospective observational study comparing outcomes application of low-frequency pulse electrical combined with target-oriented rehabilitation therapy in postoperative nerve function rehabilitation of patients with distal humeral fracture and radial nerve injury - Shi, Shaoyan; Ou, Xuehai; Du, Xiaolong (Frontiers in Neurology, 2024)
Objective The aim of the present study was to compare the effect of low-frequency pulse electrical stimulation combined with target-oriented rehabilitation therapy and single low-frequency pulse electrical stimulation therapy on postoperative neurological improvement in patients with radial nerve injury and humeral condylar fracture. Methods A total of 88 patients with humeral condyle fracture and radial nerve injury admitted to our hospital from April 2019 to January 2022 were randomly divided into a combined group and a control group, with 44 patients in each group. The patients in the combined group received low-frequency pulse electrical stimulation combined with target-oriented rehabilitation therapy, while those in the control group received low-frequency pulse electrical stimulation therapy. The recovery rate of radial nerve function, the recovery of finger extensor and wrist extensor muscle strength, and the occurrence of postoperative complications were evaluated in all patients. Results After treatment, the recovery rate in the combined group (77.27%) was higher than that in the control group (50.00%) (p < 0.05). There was no significant difference in finger extensor and wrist extensor muscle strength before treatment between the two groups (p > 0.05). After treatment, both groups showed improvement compared to before treatment (p < 0.05), and the recovery in the combined group was better than that in the control group (p < 0.05). There was no significant difference in MCV and amplitude before treatment between the two groups (p > 0.05). After treatment, both groups showed improvement compared to before treatment (p < 0.05), and the recovery in the combined group was better than that in the control group (p < 0.05). The fracture healing time in the combined group was shorter than that in the control group (p < 0.05). During the treatment period, there was one case of infection and one case of joint pain in the combined group, with a complication rate of 4.55%. In the control group, there was one case of infection and two cases of joint pain, with a complication rate of 6.82%. There was no significant difference in the complication rate between the two groups (p > 0.05). The DHI score in the combined group was better than that in the control group (p < 0.05). The ESCA score in the combined group was better than that in the control group (p < 0.05). Conclusion Low-frequency pulse electrical stimulation combined with target-oriented rehabilitation therapy can promote muscle strength and functional recovery after radial nerve injury, accelerate fracture healing time, and no additional risk of complications. Clinical trial registration https://www.researchregistry.com/, researchregistry9461.